2021
DOI: 10.1111/dar.13243
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco policy in Bangladesh: A stakeholder study of compatibility with the World Health Organization's Framework Convention on Tobacco Control

Abstract: Introduction. Smokeless tobacco (ST) is the predominant form of tobacco used in Bangladesh and is associated with adverse health outcomes. Bangladesh ratified the World Health Organization's Framework Convention on Tobacco Control (FCTC) in 2004. There are concerns that FCTC legislation and implementation of ST control policy is insufficient in Bangladesh. The aim of this study was to investigate the achievements and challenges of ST policy in Bangladesh and its alignment with the FCTC. Methods. We conducted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Despite a high disease burden associated with ST use, cessation services are not available for ST users in routine healthcare at public facilities in Bangladesh1 and integrated policy including cessation support is warranted 22 . Also, as per the participants in the present study, a dearth of research on effective contextual intervention and lack of evidence on supply chain control remain to be addressed in the country, and matches the findings of a recent study 23 . The same study also suggests that the implementation of FCTC has not been in alignment with the requirements of ST control policies and vice versa.…”
Section: Discussionsupporting
confidence: 84%
“…Despite a high disease burden associated with ST use, cessation services are not available for ST users in routine healthcare at public facilities in Bangladesh1 and integrated policy including cessation support is warranted 22 . Also, as per the participants in the present study, a dearth of research on effective contextual intervention and lack of evidence on supply chain control remain to be addressed in the country, and matches the findings of a recent study 23 . The same study also suggests that the implementation of FCTC has not been in alignment with the requirements of ST control policies and vice versa.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the present study indicated that there may be a gap in delivering messages about the harms of ST use. Recent studies reported poor implementation of graphic health warnings on ST packages in Bangladesh [36,37]. Therefore, by rotation implementation of GHWs including different tobaccorelated harm will motivate people to quit tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with a previous study [ 13 ], in that those who believe tobacco use is harmful to health are more likely than others to report that they intend to quit in the future. A recent study found that relevant legislation remains ineffective in relation to graphical health warnings on SLT packets [ 28 ]. Appropriate measures need to be taken without further delay, along with specific programmes targeting SLT use to make people aware of its harmful effects.…”
Section: Discussionmentioning
confidence: 99%